AGE-RELATED MORPHOLOGICAL FEATURES OF THE INTRACRANIAL (CISTERNAL) SEGMENT OF THE FACIAL NERVE DURING THE POSTNATAL PERIOD - Kerimzade, G.E. (World of Medicine and Biology, 2025)
The study of the intratruncal structure of the facial nerve has long been a focus of interest for researchers. In this article, the age-related morphological features of the facial nerve segment extending from the base of the brain to the internal acoustic meatus were examined. The material consisted of cross-sections of the intracranial (cisternal) portion of the facial nerve, obtained from 96 human cadavers of both sexes and various stages of postnatal development. According to the case history, no pathological changes were identified in the skull or temporal bone, and no facial nerve pathologies were recorded in any of the cadavers. For histological examination, the cadavers from which the study material was obtained were divided into five age groups: group I (7–12 years) – 8 cadavers; group II (13–20 years) – 11 cadavers, group III (21–35 years) – 22 cadavers, group IV (36–57 years) – 35 cadavers and group V (58–74 years) – 20 cadavers. The samples were fixed in a solution containing 2 % paraformaldehyde, 2 % glutaraldehyde, and 0.1 % picric acid in 0.1 M phosphate buffer (pH 7.4). The results showed that in adults, the shape of the facial nerve is either oval or irregular, but its configuration is not directly related to the internal organization of the nerve. The number and arrangement of nerve bundles, as well as their myeloarchitectonic structure, are determined by the characteristics of early ontogeny. The study also found that the shape, size, number, and topography of the nerve bundles are variable parameters that depend on both individual features and age. These indicators are closely related to the connective tissue stroma of the nerve trunk.
Keywords: facial nerve; myeloarchitectonics; myelinated nerve fibers; connective tissue stroma